2017
DOI: 10.1177/1049731517715316
|View full text |Cite
|
Sign up to set email alerts
|

Employment Supports for Adults With Disabilities in Low- and Middle-Income Countries: A Campbell Systematic Review

Abstract: Thank you for choosing to publish with us. This is your final opportunity to ensure your article will be accurate at publication. Please review your proof carefully and respond to the queries using the circled tools in the image below, which are available by clicking "Comment" from the right-side menu in Adobe Reader DC.* Please use only the tools circled in the image, as edits via other tools/methods can be lost during file conversion. For comments, questions, or formatting requests, please use. Please do not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 40 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…Thus, the decisions made for the intervention planning, the continuous monitoring of the application and adaptation of the program to the participants' needs and context demands, the facilitator's experience, and the results achieved are important concerns in the search to frame this program among EBPPs. The identification of evidence-based practices in special education has been a significant advancement in the field, given that it contributes to generating more effective interventions and producing more positive results for the development of people with disabilities, as indicated by Cook and Odom (2013) and Tripney et al (2017).…”
Section: Frequency Of Process Indicators In the Record Of Sessions Obmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, the decisions made for the intervention planning, the continuous monitoring of the application and adaptation of the program to the participants' needs and context demands, the facilitator's experience, and the results achieved are important concerns in the search to frame this program among EBPPs. The identification of evidence-based practices in special education has been a significant advancement in the field, given that it contributes to generating more effective interventions and producing more positive results for the development of people with disabilities, as indicated by Cook and Odom (2013) and Tripney et al (2017).…”
Section: Frequency Of Process Indicators In the Record Of Sessions Obmentioning
confidence: 99%
“…The difficulties of including people with physical disabilities in the work world have attracted the attention of researchers and professionals (Coutinho, Rodrigues, & Passerino, 2017;Lorenzo & Silva, 2017;Tripney et al, 2017). Research has indicated that in relation to the representative number of working-age individuals with disabilities, a large portion are not included in the labor market (Brasil, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations